(untitled) (International Research in Economics and Finance, 2017)
Equity exchanges are sprouting in developing countries due to the privatization of state-owned enterprises. China officially opened its first recognized stock exchange, the Shanghai Security Exchange in December, 1990 and a few months later the Shenzhen Stock Exchange opened. This paper compares the micro-structure of the equity markets in China, Hong Kong, and Taiwan. For a foreign investor, the markets in Hong Kong contain the least restriction and are the most accessible. Both China and Taiwan impose restrictions on foreign investment. China restricts foreign investment by only allowing the purchase of B shares Chinese exchanges, while Taiwan limits foreign investors to only four investment funds. China also allows for higher commissions on foreign investor purchases. In addition, Non-Chinese investors in  shares may be subject to a 20% withholding tax on that portion of dividend income that exceeds the People’s Bank of China’s one-year rate for the same period. These discriminatory measures can be expected to have a negative impact on foreign capital inflows and to reduce the liquidity of these markets. The impact on the prices of shares and potential rates of return cannot be positive from these restrictions since, all else constant, lower demand implies lower price. It may be, however, that the inherent potential in these growing markets from recent political and economic changes may create high rates of return, despite the restrictions on capital flows. There are also other alternatives for capital inflows to direct stock investment, such as Foreign Direct Investment (FDI). FDI, in turn, may well flow through to higher stock prices.